The population-based Barcelona-Asymptomatic Intracranial Atherosclerosis Study (ASIA): rationale and design - Pera Guillem; Alzamora Maite; Galán Amparo; Mataró María; Massuet Anna; Suñol Anna; Reverté Silvia; Millán Mónica; Dorado Laura; López-Cancio Elena; Torán Pere; Dávalos Antoni; et al. (BMC Neurology, 2011)
Abstract Background Large-artery intracranial atherosclerosis may be the most frequent cause of ischemic stroke worldwide. Traditional approaches have attempted to target the disease when it is already symptomatic. However, early detection of intracranial atherosclerosis may allow therapeutic intervention while the disease is still asymptomatic. The prevalence and natural history of asymptomatic intracranial atherosclerosis in Caucasians remain unclear. The aims of the Barcelona-ASymptomatic Intracranial Atherosclerosis (ASIA) study are (1) to determine the prevalence of ASIA in a moderate-high vascular risk population, (2) to study its prognostic impact on the risk of suffering future major ischemic events, and (3) to identify predictors of the development, progression and clinical expression of this condition. Methods/Design Cross-over and cohort, population-based study. A randomly selected representative sample of 1,503 subjects with a mild-moderate-high vascular risk (as defined by a REGICOR score ≥ 5%) and with neither a history of cerebrovascular nor ischemic heart disease will be studied. At baseline, all individuals will undergo extracranial and transcranial Color-Coded Duplex (TCCD) ultrasound examinations to detect presence and severity of extra and intracranial atherosclerosis. Intracranial stenoses will be assessed by magnetic resonance angiography (MRA). Clinical and demographic variables will be recorded and blood samples will be drawn to investigate clinical, biological and genetic factors associated with the presence of ASIA. A long-term clinical and sonographic follow-up will be conducted thereafter to identify predictors of disease progression and of incident vascular events. Discussion The Barcelona-ASIA is a population-based study aiming to evaluate the prevalence and clinical importance of asymptomatic intracranial large-artery atherosclerosis in Caucasians. The ASIA project may provide a unique scientific resource to better understand the dynamics of intracranial atherosclerosis from its early stages and to identify new potential therapeutic targets for this condition.